Integrated gas sensor development for IoT applications - Koh, Martin Teck Wee (2018)
Gas detection technology has been explored extensively and has become more significant due to its inclusion in wide range of applications. Some examples include polluting gas detection by vehicles in the automotive industry, indoor air quality (IAQ) monitoring, environmental studies and detection of alcohol level in breath analysis. Gas sensors for Consumer Electronics applications play an important part and are expected to reach 350 million units by 2021, growing at a compound annual growth rate (CAGR) of 49%. The gas detection is highly dependent on the design of the photoacoustic cells and the transducer sensitivity. MEMS Microphone is the transducer discussed in this project. MEMS Microphone offers high signal to noise ratio (SNR), low power consumption and better sensitivity. In this project, the photoacoustic cell will be designed based on the highest-pressure sensitivity of the MEMS microphone.